Slope Disaster Monitoring and Management - Zhang, Yunlong (International Journal of Natural Resources and Environmental Studies, 2025)
In the process of engineering construction, slope geological disasters are a difficult problem in safety management. Slope monitoring can effectively predict the occurrence of landslides. This article takes the Xianggang Mountain slope in Baohan Zhijie as an example to predict the displacement of the slope in the past two years and make a reasonable analysis of its stability; There are various techniques for slope treatment and reinforcement, and it is crucial to analyze and explore the causes of slope disasters, and take effective treatment measures based on terrain, geomorphology, and geological conditions. This article combines the actual situation of the Maoming open-pit mine slope geological disaster prevention and reinforcement project to deeply explore the governance technology, which has practical significance.